2019
DOI: 10.1096/fj.201901604r
|View full text |Cite
|
Sign up to set email alerts
|

Removal of artifact bias from qPCR results using DNA melting curve analysis

Abstract: Quantitative PCR (qPCR) allows the precise measurement of DNA concentrations and is generally considered to be straightforward and trouble free. However, analyses using validated Sybr Green I-based assays regularly amplify both the correct product and an artifact. Amplification of more than 1 product can be recognized when melting curve analysis is performed after the qPCR. Currently, such reactions need to be excluded from further analysis because the quantification result is considered meaningless. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 25 publications
0
24
0
Order By: Relevance
“…In this study, we did not validate our RNA-seq data using qPCR. While this may be seen as a limitation of the study, qPCR can be highly biased as it depends upon primer sequence design, variances in the target annealing temperatures, and the fact that results are usually referenced to a reference gene [ 45 , 46 ]. RNA-seq, in contrast, minimizes these inherent biases, especially the ones related to unforeseen variances in the reference gene due to experimental conditions, as the raw mRNA fragments are sequenced and aligned to the entire genome, thus providing an unbiased view of gene expression across all samples.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we did not validate our RNA-seq data using qPCR. While this may be seen as a limitation of the study, qPCR can be highly biased as it depends upon primer sequence design, variances in the target annealing temperatures, and the fact that results are usually referenced to a reference gene [ 45 , 46 ]. RNA-seq, in contrast, minimizes these inherent biases, especially the ones related to unforeseen variances in the reference gene due to experimental conditions, as the raw mRNA fragments are sequenced and aligned to the entire genome, thus providing an unbiased view of gene expression across all samples.…”
Section: Discussionmentioning
confidence: 99%
“…Substitution of Equation ( 8) into Equation (11), cancelling out N q and subsequent rearrangement results in the classic equation for efficiency-corrected relative quantification [14]:…”
Section: Bias In Fold Effect or Treatment/control Ratiomentioning
confidence: 99%
“…Using a dataset with 93 validated assays, we have shown that amplification of nonspecific products occurs frequently, and that amplification of these products cannot simply be identified from a deviating PCR efficiency or a high C q value, indicated by the slopes and the positions of the amplification curves, respectively [12]. The PCR efficiency observed for reactions that amplify correct products, artefacts or both, are indistinguishable (Figure 7A) [11]. Although the C q value distributions overlapped for all assays, only 5% of the reactions that amplified only correct products had a C q above 34, whereas only 5% of the reactions with a C q under 27 amplified an artefact.…”
Section: Q and Artefact Amplificationmentioning
confidence: 99%
See 2 more Smart Citations